The Science Delusion: Freeing the Spirit of Enquiry by Rupert Shelrake - Wolf, Fred (Journal of Scientific Exploration, 2012)
Dr. Sheldrake, an eminent biologist and creative thinker, astounded the scientific world in 1981 with his first book, A New Science of Life. Sheldrake posited the view that nature contains within her breast, fields that guide and change life forms. He called them morphogenetic fields, which I will label simply as MG-fields. In September, 1981, John Maddox, a senior editor of Nature, published an Editorial concerning Sheldrake’s opening opus entitled “A Book for Burning?” In it, Maddox said: Sheldrake’s argument is an exercise in pseudo-science. Many readers will be left with the impression that Sheldrake has succeeded in finding a place for magic within scientific discussion—and this, indeed, may have been a part of the objective of writing such a book. Maddox did not act concerned by the criticism his “burning” comments received, and elaborated on his views: “Sheldrake’s [view] can be condemned in exactly the language that the Pope used to condemn Galileo, and for the same reasons: It is heresy.” Therein lays the crux, as they say. Scientists, perhaps exhibiting the very same heretical morphogenetic field of the past clerics surrounding Galileo’s time—who abhorred any publishing of anti-clerical views—have seemingly adopted a similar abhorrence in their reluctance to accept within scientific legitimacy anything to do with what cannot be demonstrated by means brought forward via materialistic demand. Or perhaps scientists are in morphogenetic resonance with the field of Bruno at the burning stake; they have adopted a closed and fearful mindset when it comes to going beyond the bounds of materiality. No one will strike the match of illumination to examine the boundary between materialistic and non-materialistic causation, and thus all enquiries in this matter are to be left unstated; “Don’t ask, don’t tell” is alive and well within the “sacred” halls of science.